(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2025)
This work presents the isolation and characterization of two natural products from the root extract of Acanthus montanus. Extract of the root was acquired by means of maceration using n-hexane and ethyl acetate sequentially. The ethyl acetate extract was fractionated via vacuum liquid chromatography and further purification through column chromatography provided two compounds (one crystalline and one amorphous). Characterization of the compounds was achieved through IR spectroscopy and NMR experiments while biological activities of the two isolates were confirmed using agar well diffusion assay. The two isolated natural products were characterized as 5- methylresorcinol and glycosylated stigmasterol having 2.6% and 1.7% yields, respectively. 5-Methylresorcinol and glycosylated stigmasterol showed biological activities against eight bacteria and seven fungal species. Zones of inhibition ranged from 25 to 39 mm against bacteria and 18 to 34 mm Dhaka Univ. J. Pharm. Sci. 24(2): 139-146, 2025 (December)